Synthesis and Characterization of Some New Pyridine and Pyrimidine Derivatives and Studying Their Biological Activities (Baghdad Science Journal, 2023)
Heterocyclic systems, which are essential in medicinal chemistry due to their promising cytotoxic activity, are one of the most important families of organic molecules found in nature or produced in the laboratory. As a result of coupling N-(4-nitrophenyl)-3-oxo-butanamide (3) using thiourea, indole-3-carboxaldehyde, or piperonal, the pyrimidine derivatives (5a and 5b) were produced. Furthermore, pyrimidine 9 was synthesized by reacting thiophene-2-carboxaldehyde with ethyl cyanoacetate and urea with potassium carbonate as a catalyst. The chalcones 11a and 11b were synthesized by reacting equal molar quantities of 1-naphthaldehyde and 2-quinoline carboxaldehyde with 4-Bromo acetophenone and 4- fluoro acetophenone respectively. Pyrimidine 13 was synthesized by reacting chalcone 11a with guanidine hydrochloride in the presence of potassium hydroxide. Pyridine derivative 14 was prepared from the reaction of chalcone 11b with ethyl cyanoacetate and ammonium acetate in glacial acetic acid. In addition, the reaction of 4-methyl benzaldehyde and 4-fluoro acetophenone with ethyl cyanoacetate and ammonium acetate in n-butanol gave pyridine derivative 16. Spectral investigations (FT-IR, 1H, and 13C-NMR) and EI-MS spectra were used to determine the structure of the prepared compounds. The synthesized derivatives were tested in vitro for their potential cytotoxicity against two different human cancer cell types, MCF-7 (breast cancer cell) or HepG2 (liver cancer cell). Compounds 5a and 14 displayed cytotoxic activity versus HepG2 cell line with IC50 values of 43.84 and 57.14 µg /mL, respectively. Furthermore, the pyridine compound 14 demonstrated cytotoxic action versus MCF-7 with an IC50 value of 50.84 g/mL. The antibacterial and anti-parasitic properties of the synthesized derivatives have also been described.